Assessing the factor structure of the Eating Attitude Test-26 among undergraduate students in Malaysia - Wider, Walton; Mutang, Jasmine Adela; Chua, Bee Seok; Lin, Jiaming; Kamu, Assis; Pang, Nicholas Tze Ping (Frontiers in Nutrition, 2023)
The objective of this study was to assess the factor structure of the 26-item Eating Attitude Test (EAT-26) through Confirmatory Factor Analysis (CFA) among 1084 undergraduate students in Malaysia. The initial findings indicated a lack of support for the proposed three-factor structure.Model modifications were made due to the inadequate initial fit. The fit of the model was significantly improved by excluding items with factor loadings below 0.40 and integrating residual covariances. In conclusion, it is necessary to make contextual modifications to the EAT-26 in order to effectively utilize it among Malaysian undergraduates. This highlights the significance of cultural adaptations in psychological instruments.